A DISTRIBUTED MORPHOLOGY ANALYSIS OF INDONESIAN KE-/-AN VERBS - Hidajat, Lanny (Linguistik Indonesia, 2014)
Indonesian ke-/-an verbs have a complex argument structure. Similarly to Indonesian passive di- verbs, ke-/-an verbs never have an agentive NP in the subject position and their subject NPs must be definite. However, unlike passive di- verbs, these verbs generally cannot be followed by an agentive prepositional phrase. In addition, when ke-/-an verbs have two arguments, the applied argument appears in the subject position instead of the internal one. In this study, the structure of Indonesian ke-/-an verbs is analyzed by using the Distributed Morphology framework (Folli dan Harley, 2002; Kratzer, 1996; Marantz, 1997; among others). Based on the verbs’ distribution and interpretation, this study argues that of ke-/-an verbs are derived by attaching the ke-/-an circumfix, which is an overt representation of a verbalizing head, to the projection ofROOT.